Social and Systemic Influences on International Students’ Choice of a STEM Major - Shiva Jahani, Ph.D.; Rebecca Soto (Journal of International Students, 2024)
Countless factors influence students’ educational and career choices. We examined potential impacts on international students’ choices to study STEM (science, technology, engineering, or math) through the lens of Social Cognitive Theory (Bussey & Bandura, 1999). Using partial least squares structural equation modeling (PLS-SEM), we analyzed the dataset with ten gender- and finance-related constructs as explanatory variables that impact the salience of various reasons for selecting a STEM major. Financial considerations and the availability of government-funded opportunities, women’s lack of prominence in respondents’ higher-education experiences and the availability of government-funded opportunities, and (a) job outlooks for women and the "chance to help others" and (b) women’s lack of prominence in secondary education and the prospect of steady employment showed significant influence. These findings support the salience of financial concerns and gender-stereotyped, patriarchal culture influencing respondents to choose STEM majors for financial safety and/or egalitarianism.